Firm’s accountability: does it changes the impact CSR motivations have on consumer’s purchase intention? - Miranda, Joana Maria da Silva Gonçalves (2018)
Today’s economic and social conjuncture has led to a change in companies’ approach and consumers’ perception towards Corporate Social Responsibility (CSR). This dissertation studies the impact that CSR perceived motivations have on consumers’ purchase intention and the effect firm’s accountability has in this relationship. Results demonstrate that motivations solely do not impact consumers’ purchase intention. Nevertheless, consumers’ purchase intention is enhanced when values and stakeholder motivations are perceived and when firms are accountable. This moderating effect of accountability demonstrates that managers, to improve financial outcomes, should adapt their CSR communication strategy, focusing it on stakeholders’ demands and firm’s social values.